Dampak Pelatihan, Motivasi Dan Lingkungan Kerja Pada Kinerja Karyawan PT KAI (Persero) Di Stasiun Surabaya Pasar Turi - Amanda Putri Herman Boedhiarti; Hesti Pandu Widodo; Achmad Daengs GS; Sugiharto Sugiharto; Bambang Karnain; Rina Dew; Gede Wiyasa (Journal of Management and Creative Business, 2024)
The research aims to analyze the influence of training, motivation and work environment on the performance of PT KAI (Persero) employees at Pasar Turi Station, Surabaya. Quantitative research method with  questionnaire instruments. Sample of 60 employees and data analysis using multiple linear regression. The research results partially prove that training has a significant effect on employee performance. partially work motivation has a significant effect on employee performance. partially the work environment has a significant effect on employee performance. Simultaneously training, motivation and work environment have a significant effect on employee performance.